Water Encyclopedia: Hydrologic Data and Internet Resources, The, Third Edition - Fierro, Pedro Jr. (CRC Press, 2009)
"Just do an Internet search." "It's on the Internet" These phrases have quickly become a part of the vernacular. The quintessential book of data relating to water, The Water Encyclopedia: Hydrologic Data and Internet Resources, Third Edition arose from the premise that most of the information provided within this publication could be easily found on the Internet. As the editors and their team of contributors soon discovered, using the Internet for research can be problematic. Too much, too little, and questionable data sets can influence the caliber of your results.